Effective treatment for electronic waste - Selective recovery of copper by combining electrochemical dissolution and deposition. (20th May 2017) - Haccuria, E.; Ning, P.; Cao, H.; Venkatesan, P.; Jin, W.; Yang, Y.; Sun, Z.
Abstract: The difficulties for selective metal recovery from electronic waste are induced by the high complexity of such waste stream and complicated purification procedures. In this research, an electrochemical stimulated method is demonstrated to selective recover copper from an industrially provided electronic waste. More specific, one-step selective copper recovery was achieved by combining electrochemical dissolution and deposition in ammonia-based electrolyte. In the process, copper instead of other impure metals from the electronic waste is selectively dissolved and electrochemically enhanced at the anode. On the other side of the cell, pure copper was electrodeposited at the cathode. The current efficiency was found to be significantly influenced by the applied current density if galvanostatic process was facilitated. Both temperature and copper concentration in the electrolyte were found to have positive effects on the current efficiency. In a well-controlled process, copper of 99.56 wt% purity can be obtained which can be further improved by preventing potential oxidation on the electrodeposited layer. This research provide a possibility for selective copper recovery in one-step by substantially decreasing the purification cost and simplifying copper recovery procedures from electronic waste. Highlights: Direct and selective copper recovery from electronic waste is achieved. Current efficiency in the process reaches more than 90%. Pure copper with purity of 99.56% can be obtained.